Penerapan Reward Dan Punishment Dalam Meningkatkan Kedisiplinan Siswa Di Kelas IV Mi Miftahul Ulum Pandan Arum - Sayid Ahmad Fauzi; Benny Angga Permadi (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2023)
Reward and punishment are part of the motivation for students to be better whose aim is to change a person's behavior so that the student becomes disciplined. Discipline is one of the good and commendable characteristics that can support and influence success in the educational process, so that if the attitude of discipline in learning has been instilled from an early age then a character and educational goals will be achieved with satisfactory results. This study used a qualitative research method with a descriptive approach. Data collection techniques used are observation, interviews and documentation. He results of the study stated (1) the application of reward and punishment in class IV MI Miftahul Ulum was by giving rewards in the form of praise, gifts and plus points. While the application of punishment in class IV MI Miftahul Ulum is by giving warnings and punishments in the form of picking up trash, standing in front of the class, getting low scores and writing sentences on the blackboard or in books. (2) the impact of implementing reward and punishment in class IV MI Miftahul Ulum is in the form of a positive impact on implementing rewards, namely motivating students to always do good, be happy and enthusiastic during the teaching and learning process and be disciplined. The negative impact of rewards is feeling arrogant and doing something just to get gifts and praise. While the positive impact of punishment is motivating students not to repeat their mistakes and always obeying school rules and giving a deterrent effect. The negative impact of implementing punishment is that there are some students who do not obey the teacher's orders.